Marketing and competitiveness plan of a financial institution in Peru - ROSILLO ALBERCA, Alberto (2020)
The main objective of this research was a marketing plan based on a saving and credit union based on theories of service marketing to improve competitiveness. Therefore, it focused on addressing service marketing strategies to go up the levels of customer acquisition and retention in the diverse offer of its products, both in passive operations (deposits) and in active operations (placements) and this way improve your position in the ranking of cooperatives. A descriptive quantitative methodology was followed, using the survey and the interview as techniques. IBM SPSS Statistics v.22 software was used, using descriptive statistics; where it was possible to identify the most relevant characteristics of the problem, both in its origin and in its development, and based on it, tables and figures showing the frequencies and percentages have been prepared. The results revealed that there are many deficiencies that must be taken into account by the cooperative, so that with the implementation of the marketing plan they contribute to improving competitiveness, which in turn are successful in differentiating from the competition by being a leader in the sector.Keywords: marketing plan, competitiveness.